Desenvolvimento sustentável versus decrescimento: educação ambiental, cidadania ambiental e o modelo técnicopedagógico de agenda ambiental escolar da Secretaria de Educação do Município de Manaus - Dantas, Thiago Braga (2011)
The purpose of this study is to examine if the Technical-pedagogic Model of Scholar Environmental Agenda of the city of Manaus is able to develop environmental citizenship in the critical perspective for the sustainable development which takes effect on de-growth. Such problem is due to the inability of the principle of sustainable development deal adequately the environmental crisis. Accordingly, by the critical path of the de-growth, environmental education is the first step for the formatting of this counterculture as a tool indispensable to the exercise of environmental citizenship. For this, it will proceed to the critical vision of sustainable development by through the prospect of de-growth. From this contraposition, it will penetrate to the realm of environmental education, evaluating which chain - conservative and non conservative - will be able to generate environmental citizenship along the lines of the counterculture of the de-growth. According to the goal drawn, as for the methodology, it will be used the deductive method of approach and the historical and comparative methods of procedure, without forgetting the research technique of indirect documentation, in both forms: bibliographical and documental. Therefore, it is concluded that the environmental education promoted by the Technical-pedagogic Model of Scholar Environmental Agenda of the City of Manaus is not capable of generating environmental citizenship in the manner of the de-growth, because the technical-pedagogic model is guided by the conservative environmental education, which caters to the designs of dynamic conservatism which is the principle of sustainable development, moving away from the slope of non conservative environmental education, unique chain of environmental education that can provide the critical foundation necessary for the performance of environmental citizenship in the manner of de-growth, enable to face the complex socioenvironmental problems in the city of Manaus